Association Between Dental Calculus and Hypertension Phenotypes in Highly Fit Adults: CHIEF Oral Health Study. (21st October 2022) - Tsai, Kun-Zhe; Huang, Ren-Yeong; Cheng, Wan-Chien; Han, Chih-Lu; Huang, Wei-Chun; Sui, Xuemei; Lavie, Carl J; Lin, Gen-Min
Abstract: Background: Poor oral health evaluated by presence of dental calculus has been associated with hypertension (HTN) among middle- and old-aged adults. However, it is unclear for the association of HTN phenotypes with dental calculus in young adults. Methods: This study examined the association between dental calculus and HTN in 5, 345 military personnel, aged 19–45 years, without antihypertensive medications therapy in Taiwan from 2018 to 2021. Dental calculus was defined as presence of supragingival calculus in any teeth, except impacted teeth, and third molar. Combined HTN (CHTN) was diagnosed as systolic blood pressure (SBP) ≥130 mm Hg and diastolic blood pressure (DBP) ≥80 mm Hg. Isolated systolic and diastolic HTN were, respectively, defined as SBP ≥130 mm Hg only (ISHTN) and DBP ≥80 mm Hg only (IDHTN). Multiple logistic regression with adjustments for sex, age, toxic substance use, anthropometrics, lipid profiles, fasting glucose, and blood leukocyte counts were used to determine the association between dental calculus and HTN phenotypes in young adults. Results: The prevalence of those with dental calculus, CHTN, ISHTN, and IDHTN was 20.8%, 10.8%, 10.2%, and 7.0%, respectively. The dental calculus was associated a greater possibility with CHTN [odds ratio (OR) and 95% confidence interval: 1.60 (1.31–1.95)]. However, the associations of dental calculus with ISHTN and IDHTN were null [OR: 1.05 (0.81–1.27) and 1.12 (0.86–1.46), respectively]. Conclusions: Our findings suggest that among young adults, poor oral health manifested by presence of dental calculus was associated with a greater possibility of CHTN, while not for ISHTN and IDHTN. Graphical Abstract: